Impact of programmed cell death protein 1 inhibitor therapy on the survival of patients with advanced or recurrent uterine cancers: a meta-analysis - Liang, Keng-Wei; Chen, Liang-Jou; Wang, Chun-Hao; Ma, Kevin Sheng-Kai; Hsia, Li-Hsin; Wang, Po-Hui (Frontiers in Immunology, 2024)
No prior meta-analysis has investigated the impact of programmed cell death protein 1 (PD-1) inhibitor therapy on survival outcomes in patients with advanced or recurrent uterine cancers (including both corpus and cervical cancers).A comprehensive search of PubMed and Embase databases was conducted, covering the past 10 years (up to August 2023) and encompassing all clinical research related to uterine cancer. Five randomized controlled trials and one cohort study met the inclusion criteria and were included in the meta-analysis. Data on patient demographics, clinical characteristics, treatment regimens, and survival outcomes were extracted. Hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), as well as the relative risk of grade 3 or higher adverse events, were pooled using randomeffects models.Results: Patients receiving PD-1 inhibitors had better OS (HR, 0.65, 95% CI, 0.59-0.72; P<.001) and PFS (HR, 0.59, 95% CI, 0.49-0.70; P<.001) than those receiving variable non-PD-1 inhibitor therapies among 3452 uterine cancer patients. The leave-one-out meta-analysis of the HR of OS showed no individual study impact on the estimation of the overall effect size. Subgroup analysis revealed better OS in the PD-1 inhibitors use than the controls in cervical cancer (HR, 0.68, 95% CI, 0.59-0.79), endometrial cancer (HR, 0.62, 95% CI, 0.54-0.72), and pembrolizumab use (HR, 0.66, 95% CI, 0.57-0.75) subgroups. Patients with advanced cervical cancer, who had CPS > 1, receiving PD-1 inhibitors have statistically significant benefits in OS compared to controls (HR, 0.65, 95% CI, 0.53-0.80). The pooled HR for overall survival was 0.71 (95% CI, 0.60-0.82; P<.001) in patients who received PD-1 inhibitors as compared to those who did not receive PD-1 inhibitors in proficient mismatch repair (MMR) endometrial cancer patients. However, in deficient MMR patients, the HR was 0.30 (95% CI, 0.13-0.70). The relative risk of grade 3 or higher adverse events was not higher in the PD-1 inhibitor group (relative risk, 1.12, 95% CI, 0.98-1.27).Survival was significantly better using PD-1 inhibitor therapy than variable non-PD-1 inhibitor chemotherapies among patients with advanced or recurrent uterine cancers.